Cytotoxic mechanisms of pemetrexed and HDAC inhibition in non-small cell lung cancer cells involving ribonucleotides in DNA - Tobias Solli Iveland; Lars Hagen; Mirta Mittelstedt Leal de Sousa; Nina Beate Liabakk; Per Arne Aas; Animesh Sharma; Bodil Kavli; Geir Slupphaug (Scientific Reports)
Abstract The cytotoxic mechanisms of thymidylate synthase inhibitors, such as the multitarget antifolate pemetrexed, are not yet fully understood. Emerging evidence indicates that combining pemetrexed with histone deacetylase inhibitors (HDACi) may enhance therapeutic efficacy in non-small cell lung cancer (NSCLC). To explore this further, A549 NSCLC cells were treated with various combinations of pemetrexed and the HDACi MS275 (Entinostat), and subsequently assessed for cell viability, cell cycle changes, and genotoxic markers. Proteomic alterations were analyzed using label-free shotgun and targeted LC–MS/MS. MS275 enhanced the sensitivity of A549 cells to pemetrexed, but only when administered following prior treatment with pemetrexed. Both HeLa (p53 negative) and A549 (p53 positive) showed robust activation of γH2AX upon treatment with this combination. Importantly, CRISPR/Cas9 knockout of the uracil-DNA glycosylase UNG did not affect γH2AX activation or sensitivity to pemetrexed. Proteomic analysis revealed that MS275 altered the expression of known pemetrexed targets, as well as several proteins involved in pyrimidine metabolism and DNA repair, which could potentiate pemetrexed cytotoxicity. Contrary to the conventional model of antifolate toxicity, which implicates futile cycles of uracil incorporation and excision in DNA, we propose that ribonucleotide incorporation in nuclear and mitochondrial DNA significantly contributes to the cytotoxicity of antifolates like pemetrexed, and likely also of fluorinated pyrimidine analogs. HDAC inhibition apparently exacerbates cytotoxicity of these agents by inhibiting error-free repair of misincorporated ribonucleotides in DNA. The potential of HDACis to modulate pyrimidine metabolism and DNA damage responses offers novel strategies for improving NSCLC outcomes.